Sickle cell disease: Awareness, knowledge and attitude among undergraduate students of a Nigerian tertiary educational institution - Ugwu, Ngozi Immaculata (Asian Journal of Medical Sciences, 2016)
Background: Sickle cell disease (SCD) is an inherited abnormality of the red blood cell characterized by chronic haemolytic anemia with numerous clinical consequences. Aims and Objectives: The objective of this study is to assess the level of awareness, knowledge and attitude to people living with SCD among undergraduate students of a tertiary educational institution in Abakaliki, South eastern, Nigeria. Materials and Methods: A cross-sectional descriptive study was carried out was carried out, and participants were selected using multistage sampling technique. Data was collected using a pre-tested, self-administered questionnaire and analyzed using SPSS software, version 20. Results: A total of 329 participants were studied, made up of 158 (48%) males and 171 (52%) females. Mean age of the participants was 22.3± 2.7years. All the participants (100%) were aware of the existence of SCD with lectures (35%) and health workers (19.1%) being the most common sources of information. One hundred and ninety one (58.1%) participants showed adequate knowledge about SCD but many of them showed some misconceptions. This study also found that majority of the participants, 291 (88.4%) have positive attitude towards people living with SCD. Majority of those who have adequate knowledge about SCD showed positive attitude while the reverse is the case for those who have inadequate knowledge. Conclusion: This study found knowledge gaps about SCD among the participants. Health education should be intensified to impact sufficient comprehensive knowledge about SCD to enable the students take informed decision about their marriage so as to prevent procreation of children affected with SCD. Asian Journal of Medical Sciences Vol.7(5) 2016 87-92